Innovative Firms or Innovative Owners? Determinants of Innovation in Micro, Small, and Medium Enterprises - de Mel, Suresh; McKenzie, David; Woodruff, Christopher (2012)
Innovation is key to technology adoption and creation, and to explaining the vast differences in productivity across and within countries. Despite the central role of the entrepreneur in the innovation process, data limitations have restricted standard analysis of the determinants of innovation to consideration of the role of firm characteristics. The authors develop a model of innovation that incorporates the role of both owner and firm characteristics, and use this to determine how product, process, marketing, and organizational innovations should vary with firm size and competition. They then use a new, large, representative survey from Sri Lanka to test this model and to examine whether and how owner characteristics matter for innovation. The survey also allows analysis of the incidence of innovation in micro and small firms, which have traditionally been overlooked in the study of innovation, despite these firms comprising the majority of firms in developing countries. The analysis finds that more than one-quarter of the microenterprises are engaging in innovation, with marketing innovations the most common. As predicted by the model, firm size has a stronger positive effect, and competition a stronger negative effect, on process and organizational innovations than on product innovations. Owner ability, personality traits, and ethnicity have a significant and substantial impact on the likelihood of a firm innovating, confirming the importance of the entrepreneur in the innovation process.